Gradual Temperature Rise in Radiofrequency Ablation: Enhancing Lesion Quality and Safety in Porcine Myocardial Tissue - Cheol-Min Lee; Jae-Young Seo; Jin-Chang Kim; Min-Ku Chon (Bioengineering)
Radiofrequency ablation (RFA) is a pivotal therapeutic technique for various medical conditions, including cardiovascular disease and oncological conditions such as liver and lung cancer. The energy-controlled mode in RFA procedures allows for uniform energy delivery but is less safe compared to the temperature-controlled mode. Therefore, it is necessary to develop a protocol that ensures safety while efficiently delivering energy in the temperature-controlled mode. In this study, we compared lesion formation using the gradual-temperature-rise mode to the fixed-temperature mode. We evaluated the lesion size, energy, cumulative time efficiency, and procedural safety in both in vitro and in vivo experiments with porcine myocardial tissue. Three experimental groups (n = 6) were compared to assess the effect of gradual-temperature-rise and fixed-temperature ablation modes. Five experimental groups (n = 6) were used to determine the optimal temperature turn-up time. The gradual-temperature-rise mode ablated larger lesions (10.48 ± 0.56 mm) compared to the 75 °C (7.67 ± 0.37 mm) and 85 °C (8.05 ± 0.36 mm) fixed-temperature groups (p = 0.002). The optimal turn-up time for efficient lesion formation was found to be between 120 and 180 s. The in vivo experiments validated the safety and efficacy of the optimized gradual-temperature-rise mode. Therefore, using the gradual-temperature-rise mode of temperature-controlled RFA enhances lesion formation, energy transfer, and safety, making it a promising approach for clinical application in cardiac ablation procedures.